AKOMODASI KOMUNIKASI ANTAR MAHASISWA ETNIS VIETNAM UNIVERSITAS ISLAM NEGERI SULTAN SYARIF KASIM RIAU DENGAN MASYARAKAT KOTA PEKANBARU - Dana, Mulia Putri; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The process of interaction in different cultural happening in society. In the process there is an understanding on the role of verbal communication and nonverbal communication, which is based on the belief that people from different cultures can adjust to accommodate other cultures. In the communication accommodation, there is a strategy used to align the communication process is being carried out, such a strategy is the convergence, divergence, and overaccommodation label. This study aims to determine the forms of accommodation such as strategy in the strategy of convergence, divergence and overaccommodation label to the communications made by the Vietnam Ethnic students and the people in Pekanbaru.To uncover these issues thoroughly and deeply, in this study is used descriptive qualitative method possible and the use of symbolic interaction approach. Data collection technique used observation, interview, and documentation. To confirm the validity of the data is done through the extension of participation and triangulation data. Informants in this study were 8 determined by purposive sampling.The results of this study indicate that the forms of convergence strategies undertaken by Vietnam Ethnic students and the people in Pekanbaru is to use Bahasain good and right way, adjust the speed and volume of sound, adjust clothing used when communicating. Forms divergence strategy is to use a different language tothe communicator, creating body movements indicate disinterest, dominating the volume and speed of speech respectively, making distance limitations. Then cause overaccommodation label is due to misunderstanding the intent to use the language of the speaker and also because excessive body movement. Objectives to be obtained in order to create balanced communication between Vietnam Ethnic students and the people in Pekanbaru.Keywords: Accommodation Communications, Student, Ethnic, Pekanbaru